Intersectionality as a theoretical-methodological contribution in research with/for/about children and infancy in intercultural contexts - Flavio Santiago; Artur Oriel Pereira; Daniela Carolina Ernst (University of Bologna, 2024)
In Brazil, childhood is built on a racist, sexist, and classist history, and studies on it are intricately woven into this reality (Arroyo, 2018). In this context, intersectional Black feminist epistemology has been conquering political and academic spaces by promoting debates to understand the mechanisms of exclusion and social inequalities. Based on this, this essay seeks to discuss intersectionality as a theoretical-methodological approach to analyze race and gender relations in childhood research with/for/about children in intercultural contexts, articulating it in the discussions of Afro-Brazilian (Bairros, 2008; Carneiro, 2011; Gomes, 2019; Gonzalez, 1983; Silva, 1998) and African-American (Collins, 1990; Crenshaw, 2002; Davis, 2016; hooks, 2018; 2020) researchers, considering the lives of children and the ways of producing research. Works carried out based on an intersectional perspective (Pereira, 2020; Santiago, 2019) help researchers and point out that in the relationships established in the daily life of early childhood education, situations referring not only to the subordination of children to adults, but also to racism, sexism, and class oppression emerge, and analyzing experiences in this space from just one of these poles is insufficient.